The effects of Picture Series strategy in improving students’ writing procedure text ability at SMP Budi Mulia, Mamuju - St Nurfadillah (Lingedu: Journal of Linguistics and Education, 2026)
This type of research a classroom action research that aims to improve writing skills through the picture series method in English language learning. The subjects of this study were 35 students of class IX SMP Budi Mulia. Mamuju district. The learning process is carried out during (online). The data collected consisted of data on student learning outcomes through learning outcomes tests in each cycle and data on student learning activities in learning through observations made. Student learning outcomes data were analyzed using means and percentages, while data on student learning activities were analyzed using procedure text analysis.The results of this study indicate that there is an increase in students' procedure text writing skills in each cycle. Based on the data on the diagnostic test results. the mean score ot students was 52.94 with a success percentage of 29%, cycle an average score of 58.82 and a success percentage of 56%. cycle Il with an average score of 66.26 and a success percentage ot 65%. while cycle the average value is 72.11 and the percentage of success is 82%. Based on the observations, the student learning activity data also experienced an increase. This can be seen from the students' responses to the material being taught. Therefore, it can be concluded that the application of the Picture Series Method can improve the procedure text writing skills of grade IX students of SMP Budi Mulia.